2019
DOI: 10.1016/j.nmni.2018.08.017
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Anaplasma phagocytophilum and Coxiella burnetii in Ixodes ricinus ticks in Switzerland: an underestimated epidemiologic risk

Abstract: Ticks are vectors of several microorganisms responsible for infectious diseases in human and animals, such as Anaplasma phagocytophilum and Coxiella burnetii. In this study, we investigated the prevalence of these two bacteria in 62 889 Ixodes ricinus ticks in selected regions covering all Switzerland. A high prevalence of 11.9% of A. phagocytophilum DNA was observed by real-time PCR on 8534 pools of ticks. This pool prevalence corresponds to an estimated prevalence of 1.71% in individual tick. A total of 144 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 25 publications
(36 reference statements)
2
11
0
1
Order By: Relevance
“…The largest sampling size of 62,889 ticks, exclusively I. ricinus, was collected in a study in Switzerland. No C. burnetiipositive tick was detected by using ompA as the target gene in this study (78). Also, 16S ribosomal RNA (rRNA) sequencing was used for the detection of Coxiella spp.…”
Section: Detection Methodsmentioning
confidence: 81%
“…The largest sampling size of 62,889 ticks, exclusively I. ricinus, was collected in a study in Switzerland. No C. burnetiipositive tick was detected by using ompA as the target gene in this study (78). Also, 16S ribosomal RNA (rRNA) sequencing was used for the detection of Coxiella spp.…”
Section: Detection Methodsmentioning
confidence: 81%
“…However, evidence is growing that for many vector-borne pathogens, the prevalence in vectors is very low and transmission is inefficient. For example, tick-borne encephalitis virus prevalence was 0.5–2% in Ixodes ricinus in endemic areas [86] and 1.7% of the same species of tick were infected with Anaplasma phagocytophilum in Switzerland [87]. Even if transmission is infrequent in nature, this may be sufficient to maintain and spread the pathogen in the population.…”
Section: Resultsmentioning
confidence: 99%
“…With the introduction of PCR methods, several studies investigating the prevalence of tick-borne pathogens in Europe showed C. burnetii DNA in over 10% of the examined arthropods [20,21]. Contrary, in other studies, no C. burnetii-specific DNA was detected in ticks [22][23][24]. In addition, tick feces samples were found to contain C. burnetii or DNA of this agent [17,25].…”
Section: Introductionmentioning
confidence: 99%